PENGARUH PERBANDINGAN VOLUME FASA AIRDENGAN FASA ORGANIK DAN KONSENTRASI AgDALAMFASA AIR PADA EKSTRAKSI PERAKDARI LIMBAH FOTO ROENTGEN - Minasari, Minasari; Kurniasih, Yeti; Ahmadi, Ahmadi (IKIP Mataram, 2016)
Roentgen photo waste containing silver metal ion (Ag+) in form of silver thiosulfic complex ([Ag(S2O3)2]3-) that danger for health and environment. To prevent contamination to environment by silver metal from roentgen photo waste, separation become need to do. Solvent extraction was one of available separation technique on this case. The aim of this research was to evaluate the influence of few extraction parameters that was water-organic phase ratio and Ag concentration on water phase to silver extraction percentage, and apply optimum condition to roentgen photo waste sample. Silver extraction was applied on various water-organic phase ratios, there were 5 : 10; 10 : 10; 25 : 10; 50 : 10; and 75 : 10 mL and various silver concentration on water phase, there were 10, 20, 30, and 40 ppm. Ag+ ion concentration was measured by AAS in 328.22 nm wavelength before and after extraction process, than calculation of silver extraction percentage could be conducted. Based on research result, optimum condition of silver extraction was obtained on 1 : 2 of water-organic phase ratio and 10 ppm of Ag concentration on water phase. 10,27 % silver extraction was obtained on application of optimum extraction condition on roentgen photo waste.